Spatial wage gaps and frictional labor markets - Sebastian Heise; Tommaso Porzio (Federal Reserve Bank of New York, 2019)
We develop a job-ladder model with labor reallocation across firms and space, which we design to leverage matched employer-employee data to study differences in wages and labor productivity across regions. We apply our framework to data from Germany: twenty-five years after the reunification, real wages in the East are still 26 percent lower than those in the West. We find that 60 percent of the wage gap is due to labor being paid a higher wage per efficiency unit in West Germany, and quantify three distinct barriers that prevent East Germans from migrating west to obtain a higher wage: migration costs, workers' preferences to live in their home region, and more frequent job opportunities received from home. Interpreting the data as a frictional labor market, we estimate that these spatial barriers to mobility are small, which implies that the spatial misallocation of workers between East and West Germany has at most moderate aggregate effects.
Keywords: E24; J61; O15; 330; employment; aggregate labor productivity; labor mobility; migration